UKURAN KEABSAHAN KEPUTUSAN TATA USAHA NEGARA DALAM PERSPEKTIF HUKUM ADMINISTRASI - Akhmad Nikhrawi Hamdie (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
This study aims to determine the size of the decision of state business administrative legal perpectives. In connection with the above, a judge can set aside the lower norms that are the basis of the decision, in the sense that the judge can not use it as a measurement because it is considered contrary to higher regulations. Thus, the judge can apply the above regulation as a measurement tool for evaluating the disputed State Administrative Decree.Likewise also if after the judge collects the facts and then finds, tests and believes that the making of the State Administration Decree was made with bad ethics and morals and does not carry out the general principles of good governance, then the judge can cancel the Administrative Decree